2014
DOI: 10.1177/0169796x13516351
|View full text |Cite
|
Sign up to set email alerts
|

An Individual Level Test of the “Feminization of Poverty” Hypothesis

Abstract: Feminization of poverty is a hypothesis that postulates that women experience poverty at higher rates than men. Over the years, empirical examination of this hypothesis has relied on the comparison between poverty status of femaleheaded and male-headed households due to lack of gender disaggregated data in many household surveys. However, the use of poverty among female-headed households as a representative measure of women's poverty masks the extent of poverty among women. Hence, this study uses individual ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…He found that male-headed households have a better livelihood and more asset endowment than female-headed counterparts. Owusu-Afriyie and Nketiah-Amponsah (2014) also conducted their study in Ghana by empirically tested the term “feminization of poverty” theory found that the hypothesis is affected by the education level of the individual. They also found that when education is considered, “feminization of poverty” is predominant only amongst the no and primary education associates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He found that male-headed households have a better livelihood and more asset endowment than female-headed counterparts. Owusu-Afriyie and Nketiah-Amponsah (2014) also conducted their study in Ghana by empirically tested the term “feminization of poverty” theory found that the hypothesis is affected by the education level of the individual. They also found that when education is considered, “feminization of poverty” is predominant only amongst the no and primary education associates.…”
Section: Literature Reviewmentioning
confidence: 99%